The Chinese herbal formula Free and Easy Wanderer ameliorates oxidative stress through KEAP1-NRF2/HO-1 pathway - Hong, Chunlan; Klauck, Sabine (Scientific reports, 2017)
Posttraumatic stress disorder (PTSD) gains a lot of attention due to high prevalence and strong psychological upset, but the etiology remains undefined and effective treatment is quite limited. Growing studies demonstrated the involvement of oxidative stress in various psychiatry diseases, suggesting anti-oxidation therapy might be a strategy for PTSD treatment. Free and Easy Wanderer (FAEW) is a poly-herbal drug clinically used in China for hundreds of years in the treatment of psychiatric disorder. We hypothesized that FAEW exerts clinical effects through the activity against oxidative stress with fluoxetine as antidepressant control drug. Our results revealed that FAEW significantly reduced both endogenous and H2O2-induced exogenous ROS levels in the human glioblastoma T98G and neuroblastoma SH-SY5Y cell lines. Transcriptome-wide microarray analysis indicated NRF2/HO-1 as the common target of FAEW and fluoxetine. Western blotting assay proved that the two drugs promoted NRF2 release from KEAP1 in the cytoplasm and translocation to the nuclei in a KEAP1-dependent manner, the expression of the protein HO-1 increased accordingly, suggesting the participation of KEAP1-NRF2/HO-1 pathway. The chemical constituents of FAEW (i.e. paeoniflorin, baicalin) bound to KEAP1 in silico, which hence might be the effective substances of FAEW. In conclusion, FAEW counteracted H2O2-induced oxidative stress through KEAP1-NRF2/HO-1 pathway.